Early Detection and Mapping of Dengue Fever Outbreaks in Urban Areas - Maulana, Muhammad Mico (PT. Lentera Ilmu Publisher, 2025)
Dengue Hemorrhagic Fever (DHF) poses a significant public health challenge in tropical regions like Indonesia, where environmental conditions favor the proliferation of Aedes aegypti mosquitoes. The Karya Maju Health Center, serving eight villages in South Sumatra, struggles with monitoring dengue cases due to manual data recording and limited tools for analyzing outbreak patterns. This study aims to address these challenges by developing a system for early detection and mapping of dengue outbreaks. The methodology employs Unified Modeling Language (UML) diagrams, including use case, activity, and class diagrams, to design an intuitive, user-centered system. Use case diagrams outline interactions between healthcare staff and the system, while activity diagrams map the process flow from data collection to visualization. The interface design prioritizes usability, providing stakeholders with clear and accessible tools for monitoring outbreaks. The system was evaluated through pilot testing, which confirmed its ability to meet all predefined criteria. Users found the interface intuitive, with well-structured menus and visualizations facilitating efficient interaction and data analysis. This study contributes to public health by offering a scalable and effective tool for dengue monitoring, enabling healthcare providers to proactively manage outbreaks and allocate resources more effectively.